Understanding the impact of principals’ instructional leadership on teachers’ self-efficacy in kindergartens of the Congregation of the Daughters of Mary Immaculate (DMI), Vietnam - -, Tran Thi Sen (Animo Repository, 2023)
Empirical studies indicated the effectiveness of instructional leadership on student achievement through teachers as ultimate mediators (Hallinger et al., 2015; Leithwood et al., 2020; Mora-Ruano et al., 2021; Zheng et al., 2017). In addition, there was a close connection between teachers’ self-efficacy and student learning (Shahzad & Naureen, 2017; Zee & Koomen, 2016). Thus, to fill the gap of student achievement and add more evidence to the empirical literature, this study aimed to understand the impact of principals' instructional leadership on teachers’ self-efficacy in DMI kindergartens. Specifically, the study tried to determine DMI principals’ instructional leadership practices, and understand how these practices impacted DMI teachers’ self-efficacy in teaching. This qualitative study employed descriptive, interview, and review of documents research designs. The study was conducted in five DMI kindergarten schools with 129 among 151 teachers working in these schools participated in the survey using “Principal Instructional Management Rating Scale” (PIMRS) - Teacher Short Form developed by Hallinger (2015) and 18 among these 129 teachers participated in the semi-structured interview. The study results indicated that the DMI principal practiced their instructional leadership roles with different practices. Their instructional leadership practices contributed to the development of teachers’ self-efficacy strongly by frequently promoting the improvement of teachers’ competence, confidence, and instruction, giving them emotional and spiritual encouragement, and building a healthy and supportive working environment for teachers. Specifically, among all instructional leadership practices, the principals’ practices in framing and communicating the school goals and providing the professional development increased teachers’ self-efficacy more powerfully. Other practices of the principal also impacted teachers’ self-efficacy positively. However, this impact was not as strong as the impact of the three practices mentioned above because those practices brought to teachers some negative feelings and pressure sometimes or required teachers to strive greatly and consistently to improve their instruction and the student learning. Despite four sources of self-efficacy according to Bandura’s Social Cognitive Theory, the findings of this study added two more factors that promoted the development of teachers’ self-efficacy. The first factor was teachers’ thorough preparation for their instructional plan. The second factor was the healthy and supportive working environment consisting of the principals’ closeness, availability, and dedicated support, and close relationships and mutual support among teachers.